Anodic aluminum oxide-membrane prepared in electrolyte “oxalic acid – matter with carbon nanodots” - K. O. Kudelko; L. M. Rozhdestvenska; L. M. Ponomarova; V. M. Оgenko (Хімія, фізика та технологія поверхні)
Anodic porous alumina has been studied and used as nanoscale structure, coating, template in different applications. The porous anodic alumina oxide could be described as numerous hexagonal cells and looks like cellular structure. In this work we report about results of study anodizing of aluminum with usage of electrolyte: “oxalic acid electrolyte-matter with carbon nanodots”. It was received anodic aluminum oxide-membrane with aluminum supporting; calcination was used as post treatment. The aluminum substrate allows one to fix the membrane in the cells. Methods: processes of anodizing was provided in 0.3M oxalic acid with addition of colloid system of carbon nanodots, temperature of process was controlled at range of 10 degree Celsius, aluminum foil (anode) and platinum plate (cathode) were used; thickness of aluminum foil was 0.1 µm; morphology and structure of anodic aluminum oxide-membrane were determined with usage of electron scanning microscope; the contact angle between the surface of anodic aluminum oxide-membrane and deionized water was measured with “drop” methodology. Calcium content was monitored with a conductometer. The content of proteins was determined with photometry (micro Lowry’s method). It was found that contact angle of the surface of anodic aluminum oxide-membrane obtained in electrolyte “oxalic acid-matter with carbon nanodots” and deionized water is 38 degrees. Adding colloidal system of carbon nanodots to the acid electrolyte acts as a hydrophilizer, changes the size of the porous surface: as a result, it is possible to control the porosity of the films. Calcination of anodic aluminum oxide-membrane at 500 degree Celsius lead to expansion and thinning of pore walls. Anodic aluminum oxide-membrane was tested for dialysis process for milk whey separation. The membrane obtained in electrolyte: “oxalic acid-matter with carbon nanodots” showed a greater degree of rejection of protein particles in comparison with a similar membrane obtained in electrolyte of oxalic acid. The advantage of using carbon nanodots in acid electrolyte is the simplicity and environmental friendliness of the synthesis. The approach, which involves the addition of a colloidal system with carbon nanomaterial, allows one to avoid using a strongly acidic electrolyte for obtaining membranes with smaller pores. One of the ways for using of anodic oxide aluminum-membrane is the dialysis of biological fluids, for example, milk whey.